Hsp104 suppresses polyglutamine-induced degeneration post onset in a drosophila MJD/SCA3 model. - Mimi Cushman-Nick; Nancy M Bonini; James Shorter (PLoS Genetics)
There are no effective therapeutics that antagonize or reverse the protein-misfolding events underpinning polyglutamine (PolyQ) disorders, including Spinocerebellar Ataxia Type-3 (SCA3). Here, we augment the proteostasis network of Drosophila SCA3 models with Hsp104, a powerful protein disaggregase from yeast, which is bafflingly absent from metazoa. Hsp104 suppressed eye degeneration caused by a C-terminal ataxin-3 (MJD) fragment containing the pathogenic expanded PolyQ tract, but unexpectedly enhanced aggregation and toxicity of full-length pathogenic MJD. Hsp104 suppressed toxicity of MJD variants lacking a portion of the N-terminal deubiquitylase domain and full-length MJD variants unable to engage polyubiquitin, indicating that MJD-ubiquitin interactions hinder protective Hsp104 modalities. Importantly, in staging experiments, Hsp104 suppressed toxicity of a C-terminal MJD fragment when expressed after the onset of PolyQ-induced degeneration, whereas Hsp70 was ineffective. Thus, we establish the first disaggregase or chaperone treatment administered after the onset of pathogenic protein-induced degeneration that mitigates disease progression.